If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying c + 15 = 76 Reorder the terms: 15 + c = 76 Solving 15 + c = 76 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + c = 76 + -15 Combine like terms: 15 + -15 = 0 0 + c = 76 + -15 c = 76 + -15 Combine like terms: 76 + -15 = 61 c = 61 Simplifying c = 61
| c+15=76 | | x=18+2x | | 4=s/9 | | 57-t=49 | | (x+2)/3-4x=8 | | y^2-13y+36/3y-12 | | x+3-4x=0 | | 12y=6-2x | | 3(x)=1/2x+5 | | 9+v=36 | | 7k-21=3k-5 | | 17=p-5 | | 31=3+m | | k+36=40 | | 9x^4+12x^2+4= | | 65-h=54 | | x-51=27 | | 54=6z | | 14=7r | | 8x+33=5x+87 | | 60y^2-51y-72=0 | | 3x^2-9x=30 | | d-(-4)=25 | | (2x+7)(x-8)=0 | | 3x^2+17x-12=0 | | 9g-6=3(4g+5) | | 3x^2-1/27x^6=0 | | 50=x+2y | | 8(x-1)-8=3x+5(-4+x) | | 15g^2-19gh-56h^2=0 | | -(-8n+2)=-4(-6+5n)+7n | | 2x^2-24=-8x |